Severe Bilateral Cervical Lymphadenomegaly Associated with Ethosuximide - Montenegro, Maria Augusta; Cardinalli, Izilda A.; Daiggi, Camila Maia Martin (Journal of Pediatric Epilepsy, 2020)
Lymphadenomegaly associated with antiepileptic drugs is well documented; however, severe lymphadenopathy mimicking a neoplasm is a rare adverse event associated with antiepileptic drugs. It is usually characterized by a large cervical mass associated with fever, weight loss, skin rash, and abnormal complete blood count (atypical lymphocytes, eosinophilia, and abnormal neutrophil count). In this case report, we described a child with severe bilateral cervical lymphadenomegaly associated with ethosuximide, in which excisional biopsy of the enlarged nodes was needed to establish the final diagnosis. Prognosis was excellent after drug discontinuation.
Keywords: absence; childhood; lymphadenomegaly; ethosuximide